Aguaruna Knowledge of Bird Foraging Ecology: A comparison with scientific data - Jernigan, Kevin; Dauphine, Nico (Ethnobotany Research and Applications, 2008)
We present a detailed look at local ecological knowledge (LEK) of the Aguaruna-Jívaro on plants foraged by frugivorous tropical birds. When asked how a particular plant is useful to people, Aguaruna men often mentioned whether the plant in question was eaten by birds or other animals. The Aguaruna use their knowledge about what plants particular birds eat to help them locate species when hunting. We focus on indigenous knowledge of the diet of five mainly frugivorous bird families that are of local economic importance: Cracidae (guans, chachalacas and curassows), Pipridae (manakins), Psittacidae (parrots), Ramphastidae (toucans) and Steatornithidae (Oilbird). Fieldwork took place in communities along tributaries of the upper Marañón river in the Peruvian Amazon from 2003 to 2005. Results indicate a high correspondence between western science and Aguaruna LEK. This research contributes to the larger goal of promoting dialog between indigenous and scientific systems of knowledge in the context of future conservation efforts.